The Role of Mental Imagery in Parkinson’s Disease Rehabilitation - Amit Abraham; Ryan P. Duncan; Gammon M. Earhart (Brain Sciences, 2021)
Parkinson’s disease (PD) is a disabling neurodegenerative disease whose manifestations span motor, sensorimotor, and sensory domains. While current therapies for PD include pharmacological, invasive, and physical interventions, there is a constant need for developing additional approaches for optimizing rehabilitation gains. Mental imagery is an emerging field in neurorehabilitation and has the potential to serve as an adjunct therapy to enhance patient function. Yet, the literature on this topic is sparse. The current paper reviews the motor, sensorimotor, and sensory domains impacted by PD using gait, balance, and pain as examples, respectively. Then, mental imagery and its potential for PD motor and non-motor rehabilitation is discussed, with an emphasis on its suitability for addressing gait, balance, and pain deficits in people with PD. Lastly, future research directions are suggested.